Visible‐Light‐Mediated Generation of Nitrogen‐Centered Radicals: Metal‐Free Hydroimination and Iminohydroxylation Cyclization Reactions. (28th September 2015) - Davies, Jacob; Booth, Samuel G.; Essafi, Stephanie; Dryfe, Robert A. W.; Leonori, Daniele
Abstract: The formation and use of iminyl radicals in novel and divergent hydroimination and iminohydroxylation cyclization reactions has been accomplished through the design of a new class of reactive O ‐aryl oximes. Owing to their low reduction potentials, the inexpensive organic dye eosin Y could be used as the photocatalyst of the organocatalytic hydroimination reaction. Furthermore, reaction conditions for a unique iminohydroxylation were identified; visible‐light‐mediated electron transfer from novel electron donor–acceptor complexes of the oximes and Et3 N was proposed as a key step of this process. Abstract : Divergenter SET : Die Bestrahlung von O ‐Aryloximen mit sichtbarem Licht führt zu N‐zentrierten Radikalen. Die Reaktionsbedingungen entscheiden, ob diese Radikale in einer Photoredox‐katalysierten Hydroiminierung oder in einer Iminohydroxylierung über einen Elektronen‐Donor‐Akzeptor‐Komplex cyclisieren (EY=Eosin Y).